Mooring Failure Analysis of Semisubmersible Floating Offshore Wind Turbines Considering Mooring Redundancy at Each Azimuth Angle - Shuai Hao; Xuning Zhang; Yang Yu; Bin Wang; Xingdao Bo (Journal of Marine Science and Engineering)
Semisubmersible floating structures are becoming the predominant understructure type for floating offshore wind turbines (FOWTs) worldwide. As FOWTs are erected far away from land and in deep seas, they inevitably suffer violent and complicated sea conditions, including extreme waves and winds. Mooring lines are the representative flexible members of the whole structure and are likely to incur damage due to years of impact, corrosion, or fatigue. To improve mooring redundancy at each azimuth angle around a wind turbine, a group of mooring lines are configured in the same direction instead of just one mooring line. This study focuses on the mooring failure problems that would probably occur in a realistic redundant mooring system of a semisubmersible FOWT, and the worst residual mooring layout is considered. An FOWT numerical model with a 3 × 3 mooring system is established in terms of 3D potential flow and BEM (blade element momentum) theories, and aero-hydro floating-body mooring coupled analyses are performed to discuss the subsequent time histories of dynamic responses after different types of mooring failure. As under extreme failure conditions, the final horizontal offsets of the structure and the layout of the residual mooring system are evaluated under still water, design, and extreme environmental conditions. The results show that the transient tension in up-wave mooring lines can reach more than 12,000 kN under extreme environmental conditions, inducing further failure of the whole chain group. Then, a deflection angle of 60° may occur on the residual laid chain, which may bring about dangerous anchor dragging.